Geminiviruses: Molecular biodiversity and global distribution in Jatropha. (December 2019) - More, Prashant; Agarwal, Parinita; Agarwal, Pradeep K.
Abstract: Jatropha is one of the most important crops for biodiesel production. Its yield has been severely hampered due to mosaic disease caused by geminiviruses. The Jatropha infecting geminiviruses reported from all over the world have significant genetic diversity. Begomoviruses infecting Jatropha are reported from the United States of America, Asia and Africa. There exist 85 complete nucleotide sequences of Jatropha geminiviruses, including 72 DNA-A segments, 11 DNA-B segments and 2 DNA-β sequences. Majority of submitted sequences are from Kenya and India. The different geminiviruses identify Jatropha either as their primary host or as an alternate host, for a successful infection. The geminiviruses require a specific host for causing the disease; however, reports suggest that the geminiviruses evolve to change their host plant specificity to infect a new host. Jatropha also became an alternate host to geminiviruses from other crops. In this review, we discuss the geminivirus infection process, the global spread of geminiviruses leading to change in host preferences, the array of histological, metabolic and molecular changes reported in Jatropha following geminivirus infection. Also, the importance of RNA interference (RNAi) strategy, as the forefront of research towards sustained control of geminiviral diseases, is emphasized. Highlights: J. curcas is a potential resource for biodiesel, and viral infection results in significant oil yield loss. The different geminiviruses that identify Jatropha as either primary or alternate host show broad genetic biodiversity. The geminiviruses of other crops have evolved themselves to be successful for infecting Jatropha. ·An array of histological, metabolic and molecular changes occur in Jatropha following geminiviral infection.